PENGARUH MARKET SHARE PERBANKAN SYARIAH DAN PERTUMBUHAN EKONOMI TERHADAP PENURUNAN TINGKAT PENGANGGURAN TERBUKA DI INDONESIA - Dedi - Dedi saputra; Slamet Slamet; Rika Lidyah (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2022)
This study aims to examine the influence of Market Share contained in Indonesian Islamic Banks and economic growth on the decline in the number of unemployment rates in Indonesia for the last 9 years. This study uses Islamic banking market share data contained in Islamic banking statistics from 2012-2021. The economic growth data is the total percentage of GDP at constant prices from 2012-2021 and the open unemployment rate data is the percentage of the unemployment rate registered at the BPS from the year 2012-2021. 2012-2021. This study uses Eviews 10.0 with the results of the study showing that Market share has a negative and not significant effect on the open unemployment rate while economic growth has a negative and significant effect on economic growth. It can be concluded that if the market share is greater then the open unemployment rate will decrease. Meanwhile, if economic growth increases, it will reduce the open unemployment rate.